Academic advising delivered differently: building an advising capability for regional Australian universities. Issue 5 (3rd September 2022) - Reimers, B. M.
ABSTRACT: Facing increased pressure to improve participation and attainment, and significant constraints in available revenue and resources, regional Australian universities are seeking opportunities to enhance student retention in a way that is sustainable and addresses the unique circumstances of regional universities. Whilst advising models, nationally and internationally, are predominantly concentrated on an expensive and time-poor academic workforce, it is proposed that there exists an opportunity to create an advising workforce from existing institutional support services. This paper provides an analysis of competencies required for academic advisors and suggests that a model that builds on the comprehensive knowledge about course structures and institutional rules, policy, and processes already endemic to staff providing student support services, could create an effective student success advising service using existing professional services staff.